2017
DOI: 10.1136/bmjopen-2017-016871
|View full text |Cite
|
Sign up to set email alerts
|

Does laryngeal reinnervation or type I thyroplasty give better voice results for patients with unilateral vocal fold paralysis (VOCALIST): study protocol for a feasibility randomised controlled trial

Abstract: IntroductionA functioning voice is essential for normal human communication. A good voice requires two moving vocal folds; if one fold is paralysed (unilateral vocal fold paralysis (UVFP)) people suffer from a breathy, weak voice that tires easily and is unable to function normally. UVFP can also result in choking and breathlessness. Current treatment for adults with UVFP is speech therapy to stimulate recovery of vocal fold (VF) motion or function and/or injection of the paralysed VF with a material to move i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 23 publications
0
13
0
3
Order By: Relevance
“…The CONTRACT communication study is one of a relatively small number of qualitative substudies to have been embedded within a feasibility trial with the aim of optimising recruitment and informing a future definitive trial. [55][56][57][58] Uniquely, our study drew on trial recruitment consultation audio-recordings, interviews with health professionals, children (patients) and parents. Although studies of this sort have been advocated, 38 embedded qualitative studies rarely include the perspectives of both children and their parents.…”
Section: Discussionmentioning
confidence: 99%
“…The CONTRACT communication study is one of a relatively small number of qualitative substudies to have been embedded within a feasibility trial with the aim of optimising recruitment and informing a future definitive trial. [55][56][57][58] Uniquely, our study drew on trial recruitment consultation audio-recordings, interviews with health professionals, children (patients) and parents. Although studies of this sort have been advocated, 38 embedded qualitative studies rarely include the perspectives of both children and their parents.…”
Section: Discussionmentioning
confidence: 99%
“…We attribute the long‐term stability of voice quality to restoration and preservation of laryngeal muscle innervation preventing muscular atrophy. To further affirm our experience concerning better voice results after ULR than after thyroplasty, a direct comparison study needs to be implemented as suggested by Blackshaw et al…”
Section: Discussionmentioning
confidence: 99%
“…Therapy is sometimes used preoperatively to minimize laryngeal hyperfunction and help improve voice outcomes postoperatively, despite a lack of evidence regarding the combined voice therapy and surgical approach to glottic insufficiency. [21][22][23] This study provides some evidence that this approach may not be necessary, although it is recognized that a lack of consistency in content, frequency, and type of voice therapy in treatment of glottic insufficiency renders comparison among treatment combinations difficult.…”
Section: Discussionmentioning
confidence: 99%